Hospital Advertising: Myth or Reality? - Gangopadhyay, Soumik; Bandopadhyay, Parimalendu (Indian Journal of Marketing, 2012)
Hospital in the Indian scenario was a free service provided by the government. People received the service consistently through the traditional system, except in a few cases. As the sector is getting priority among the Indian people due to versatile reasons, hence, the business opportunity of the sector is also flourishing day by day. Unlike traditional businesses, today's hospitals are promoted as a business centre, which is accepted by the Indian society. Care for a patient is getting top priority. Hence, advertisements of hospitals are also changing their direction. The article explains today's need of hospital advertisement and its modern forms.